Artificial Intelligence Adoption Drivers and Sustainable Performance in the Indonesian Telecommunications Industry - Ivan Fernaldy; Khairani Ratnasari Siregar (Return : Study of Management, Economic and Bussines, 2026)
Artificial Intelligence (AI) is increasingly being adopted as a strategic capability within the Indonesian telecommunications industry to support digital transformation, enhance operational efficiency, and achieve long-term sustainability performance amid intensifying competition. However, successful AI adoption is determined not only by technological readiness but also by organizational conditions, environmental pressures, and psychological assurances related to trust and data privacy. This study aims to examine the effects of the Technology–Organization–Environment (TOE) framework, Trust in AI, and privacy assurance on organizational Intention to Adopt AI, as well as their subsequent influence on actual AI use behavior and corporate sustainability performance within the Indonesian telecommunications sector. A quantitative research approach was employed using survey data collected from 231 managerial and technical professionals across telecommunications firms. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 software. The findings indicate that technological, organizational, and environmental readiness, together with trust and privacy assurance, have significant positive effects on Intention to Adopt AI. Furthermore, Intention to Adopt AI is found to be a strong predictor of actual AI use behavior, indicating that adoption intention translates into practical implementation rather than merely reflecting favorable attitudes. Consistent and integrated AI utilization subsequently contributes significantly to corporate sustainability performance, encompassing economic, operational, and environmental dimensions. These results suggest that the sustainability benefits of AI emerge when contextual readiness and psychological assurance jointly enable organizations to move beyond adoption intention toward sustained AI utilization. This study provides valuable insights for industry practitioners and policymakers in designing AI adoption strategies that support sustainable business performance in emerging telecommunications markets.